Environmental 238U and 232Th concentration measurements in an area of high level natural background radiation at Palong, Johor, Malaysia - Ramli, Ahmad Termizi (Elsevier Ltd., 2005)

(untitled)
Concentrations of uranium-238 and thorium-232 in soil, water, grass, moss and oil-palm fruit samples collected from an area of high background radiation were determined using neutron activation analysis (NAA). U-238 concentration in soil ranged from 4.9 mg kg-1 (58.8 Bq kg-1) to 40.4 mg kg-1 (484.8 Bq kg-1), Th-232 concentration ranged from 14.9 mg kg-1 (59.6 Bq kg-1) to 301.0 mg kg-1 (1204 Bq kg-1). The concentration of U-238 in grass samples ranged from below the detection limit to 0.076 mg kg-1 (912 mBq kg -1), and Th-232 ranged from 0.008 mg kg-1 (32 mBq kg -1) to 0.343 mg kg-1 (1.372 Bq kg-1). U-238 content in water samples ranged from 0.33 mg kg-1 (4.0 Bq L -1) to 1.40 mg kg-1 (16.8 Bq L-1), and Th-232 ranged from 0.19 mg kg-1 (0.76 Bq L-1) to 0.66 mg kg -1 (2.64 Bq L-1). It can be said that the concentrations of environmental U-238 and Th-232 in grass and water samples in the study area are insignificant. Mosses were found to be possible bio-radiological indicators due to their high absorption of the heavy radioelements from the environment.